“Asah Asih Asuh”: Learning Concept at Kasih I-CARE Nusantara Borobudur School - Pramudia, Rosa Virginia Cindy; Sarjiwo, S; Probosini, Agustina Ratri; Alfan, Syafiq Faliq (Studies in Learning and Teaching, 2025)
The school serves as a crucial setting for children's learning and personality growth. Within this environment, the essential foundations of knowledge, skills, and moral values are instilled in the younger generation. Kasih I-CARE Nusantara School reflects this principle through its vision and mission to provide quality education using the “asah asih asuh” approach. This research aims to explore the concept of “asah asih asuh” education through tembang dolanan at Kasih I-CARE Nusantara Borobudur School. The research method used is qualitative research with a case study approach. The object of the research is the concept of asah asih asuh applied in the school, while the research subjects include teacher who are also the founders of the school, 3 other teachers, 2 employees, 2 parents of students and 2 students themselves. The data collection techniques used include direct observation, in-depth interviews, and document collection. Data validity was ensured through triangulation of techniques and sources. Data analysis was conducted through three main stages: data reduction to identify key themes; data presentation to organize findings in a structured manner, and conclusion drawing to make in-depth interpretations of the data collected. Data verification was conducted directly and indirectly through the WhatsApp application to obtain additional clarification if needed. The results showed that the concept of sinau kanthi seneng can be found in the asah asih asuh education implemented at Kasih I-CARE Nusantara Borobudur School. This illustrates that the joyful learning approach not only improves learning effectiveness, but also strengthens social and emotional values that are important in the holistic development of learners.